INFLUENCE OF MOISTURE CONTENT AND LENGTH OF STORAGE ON FUNGAL INVASION OF PADDY RICE *) - DANILO E. PADERES (BIOTROPIA, 1997)
The relationship of moisture content and storage period to fungal population, seed germination, grain whiteness and translucency was determined. Various fungal species predominated at different moisture conditions and storage periods. The fungi observed belong to the groups of Aspergillus flavus-oryzae, A. glaucus, A. mdulans. A. candidus, A. versicolor, A. terreus and A. niger and  an unidentified species of Penicillium, Trichoconiella, Curvularia, Fusarium, Syncephalastrum  and Verticillium. The predominant storage fungi were A. fla\iis-oryzae and A. candidus whereas, the predominant field fungi were Trichoconiella sp., Cun-ularia sp. and Syncepfialastrwn sp. A decrease in the number of field fungi and an increase in the number of storage fungi with storage time were observed. Storage fungi were noted as early as five weeks after storage at moisture contents from 9.3 to 18.33%. The percentage germination of paddy remained high when stored at moisture contents of 9.3 to 14% but decreased with storage time at 14.5 to 18.33% moisture  content. The  percentage germination of paddy  reached  a peak  at  10-15 weeks of  storage. A  significant negative correlation between percent germination and moisture content was observed. At 14.5-18.33% moisture content, the germination of stored paddy decreased with a marked increase of storage molds. Changes  in grain whiteness was  not  affected by moisture  content. However,  a  decrease  in percent  whiteness  and translucency was noted after 25 weeks of storage.Keywords:       Stored products pests / Rice / Moisture content / Storage / Time / Fungi / Aspergillus sp. / Penicillium sp. / Trichoconiella sp. / Curvularia sp. / Fusarium sp./ Syncephalastrum sp. / Verticillium sp.